Translation and the Changing Profession: A Cross-Disciplinary Perspective - Séguinot, Candace (TTR, 2007)
AbstractDisciplines that deal with the selection, dissemination, and translating of information have had to adapt to changes that have come with the adoption of new technology. On the one level there has been a reflection in research on the responsibilities and relevance of the discipline itself and the professions associated with it. The “communication” professions have also shown a concomitant movement toward contracting rather than salaried positions, and so both the day-to-day organization of work and the institutionalized practices of entering the workforce, gaining experience, and being promoted have changed. Power relations inherent in organizational structures change as the organization of work changes, and the intrinsic values associated with professions that produce knowledge products change with reorganization as well. While technology has challenged all communication professions with change, the responses across these fields have been very different. This paper is about those differences in translation and disciplines close to translation. How has each discipline adapted (or not) to changes in the way its profession has evolved, and what does current research say about these transformations?